Protein Hydrolyzates from Changbai Mountain Walnut (Juglans mandshurica Maxim.) Boost Mouse Immune System and Exhibit Immunoregulatory Activities - Li, Jing (Evid Based Complement Alternat Med, 2018)
The Changbai Mountain walnut (Juglans mandshurica Maxim.) is a rich source of essential amino acids. Walnut dregs are byproducts of edible oil production and primarily used as fodder and fertilizers. We systematically examined the effect of three types of walnut protein hydrolyzates—albumin, glutelin, and globin—on the immune system of mice and aimed to provide the theoretical basis for developing and utilizing J. mandshurica Maxim. protein resources. In comparison with the normal control mice, those treated with different doses of walnut proteins showed improved immune indices, including organ index, spleen lymphocyte proliferation, macrophage activity, number of CD4(+) and CD8(+) T cells, immunoglobulin A (IgA) and secretory IgA content, and mRNA and protein expression levels of cytokine factors. Our results indicated that these walnut proteins may have positive effects on the immune system and perform their immunomodulatory functions by inducing splenic enlargement. These findings support the use of walnut proteins as nutritional sources to boost the immune system.